PENDIDIKAN ISLAMI DALAM NILAI-NILAI KEARIFAN LOKAL DIDONG - Eliyyil Akbar (IAIN Ponorogo, 2015)
Abstract: The treat of a identity of a country which faith in the heterogeneity by the raising conflict between ethnic, religion, race, violance is happen will be split the nationality. It is happen because the lowerance of the tolerance that is manifested in Islam that rahmatan lil 'Alamin and hinders the wishdom which was developed. In the middle of these divisions, Gayo highland area which is the area of enforcement of Islamic law which is inhabited by various tribes that able to neutralize the situation by maintaining the value of the ancestral wisdom and Islamic education live using the Didong media art. Hence the importance of the solution to address a conflict prone difference with respect local wisdom. The Didong art’s values element beauty, religious, and togetherness are transformed from local wisdom message is mukemel, orderly, loyal, Semayang-gemasih, mutentu, trustworthy, even-mupakat, alang-tulung, and bersikekemelen. Islamic education from the show of Didong cannot be separated from the customary, shari'ah, and more can be absorbed by people with such tolerance built up to create peace and create an atmosphere of Islamic shari'ah as a regional enforcer.الملخص :تهديد ذاتية الشعب الاندونسي التي جعل بينيكا توعكال ايكا كشعار الشعب بظهور نزاع القبائل والاديان والعناصر. الاجرائات العنيفة التي تجري جعلت سبب لنزاع الشعب. تلك الحادثة جرت بسبب زوال موق التسامخ الذي وجد في الاسلام